Evaluate to learn (Journal of Parents and Teachers, 2017)
The diagnostic evaluation in school often focuses on the quantitative results of the assessment instruments exhibition, when in reality should be the fruit of a process with three stakes: a first phase quantitative taking into account these results, a second phase of criterial character that identifies the underlying processes in the results, and a required third phase of contextualization of the results process that allows us to real feedback from the teaching process and learning.
Keywords: assessment criterial; regulations; diagnostic; contextualized